PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Muazar Habibi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstract : In accordance with the stages of children’s development, characteristics of how children learn, the concept of learning and meaningful learning, the learning activities for early grades of elementary school should be done with thematic learning. Integrated thematic learning is learning that uses theme to integrate some subjects so it can provide meaningful experiences to students. To enhance teachers’ ability to implement thematic learning, then it could be through training, lesson study, induction training, through independent study. Then, in addition, to support the success of the thematic learning it is necessary to improve school atmosphere, infrastructure improvement, improvement of surveillance systems, and preparation of students entering the school. Key Words: Learning and Thematic.